THE POTENCY OF PSIDIUM GUAJAVA LEAVES AS A NATURAL DISINFECTANT AND ANTISEPTIC INGREDIENT - Mahyuni, Siti; Komala, Oom; Wiendarlina, Ike Yulia; Fatah, Muhammad Fajar Saeful (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Preventing the spread of nosocomial infection are generally carried out by disinfection process of the tools to be used with chemical disinfectant such as phenol, alcohol, chlorine, iodine or sublimate. Excessive use of chemicals can cause health problems. Guava leaves (Psidium guajava L.) have long been empirically used to treat diarrhea and acne. Scientific data shows that guava leaves have positive activity against several types of pathogenic bacteria due to its tannin content. Guava leaves have the potential to be developed as a disinfectant and antiseptic material. This study aims to determine the disinfection activity of guava leaves on surgical instruments using the total plate count method, skin irritation test using patch test method and quantify the tannin content in young and old guava leaves using spectrophotometry method. The results showed that the tannin content in old and young guava leaves was 68.73 ± 0.067 mg/g (6.873%) and young 61.87 ± 0.046 mg/g (6.187%). At concentrations of 10, 20, 30 and 40% guava leaf extract were able to reduce the total plate count in surgical instrument samples by 6.85; 37; 80.82; and 83.56%. The primary irritation index of 0.05 only occurs at a concentration of 40%, classified as non-irritant. It can be concluded that guava leaves have the potential to be further developed as a natural disinfectant or antiseptic.